Identification of Heat Tolerant Cotton Lines Showing Genetic Variation in Cell Membrane Thermostability, Stomata, and Trichome Size and Its Effect on Yield and Fiber Quality Traits - Abro, Saifullah; Rizwan, Muhammad; Deho, Zaheer Ahmed; Abro, Shafiq Ahmed; Sial, Mahboob Ali (Frontiers in Plant Science, 2022)
Heat stress in cotton reduces its productivity. The development of heat tolerant cotton varieties having resilience against changing climate is feasible. The purpose of this study was to probe the genetic variability in upland cotton for heat tolerance, the association of cell membrane thermostability (CMT), Stomata and Trichome Size with cotton adaptation to high temperature and effective breeding strategy to advance the valued traits. Relative cell injury percentage (RCI %) in studied genotypes ranged from 39% to 86%.Seventeen genotypes were found heat tolerant on the basis of low RCI %, heat susceptibility index (HSI<1) and higher number of boll/plant and seed cotton yield (SCY). Scanning electron microscopy (SEM) of heat tolerant genotypes revealed the presence of different size of stomata (21.57 μm² to 105.04 μm²) and trichomes (177 µm to 782.6 µm) on leaves of selected genotypes. The regression analysis showed strong and negative association of RCI% and stomata size with SCY. However, no association was observed between trichome size, yield and fibre traits. On overall location basis, significant genotype × environment interaction was observed. All selected genotypes produced higher SCY as compared to check varieties. But stability analysis showed that the high yielding genotypes NIA-M-30, NIA-80, NIA-83 and CRIS-342 were also wide adaptive with unit regression (bi~1) and non-significant deviation from regression line (S2d~0). Ability to the combination of heat tolerant genotypes was estimated by line × tester method among nine hybrids along with their 3 testers (male) and 3 lines (females). Genotypes, CRIS-342 and NIA-Perkh were observed as best general combiners for SCY with negative general combining ability (GCA) effects for RCI%. Five hybrids showed positive specific combining ability (SCA) and heterotic effects for studied traits and found lowest for HSI. RCI% and SCY/plant displayed higher estimates of heritability and genetic advance indicating the heritability due to additive gene effects and chances of effective selection. The identified heat tolerant and wide adaptive germplasm can be further advanced and utilized in cotton breeding programs for developing heat tolerant cultivars. Selection criteria involving CMT and stomata size concluded to be an effective strategy for the screening of heat tolerant cotton.